Facilitating Nursing Participation in Family Centered Rounds: A Tale of Two Interventions - Anjali Sharma; Sandra Gage; Laura Norton; Heather Toth; Michael Weisgerber (Association of American Medical Colleges, 2013)
Abstract Patient- and family-centered rounds (PFCR) have been identified as an effective model for high-quality patient care. In 2012, the American Academy of Pediatrics published a policy statement on family-centered care recommending that physician rounds be conducted at the bedside, with the family and the bedside nurse present. At our institution, we have developed a comprehensive program to improve the performance quality and attendance of all participants on PFCR. This program of instruction has been coordinated for all rounds participants using an overriding theme, mascots, and mnemonic devices to highlight the desired qualities of each participant on PFCR. This publication focuses on a successful quality-improvement project that we implemented to increase nursing attendance on PFCR and provide instruction on desired behaviors. We include information about the mascots chosen at our institution for the purpose of providing an example of one possible scheme. The resource contains the tools we utilized to improve the quality and quantity of nursing participation on PFCR. The first tool is a needs assessment survey we administered to nurses to gain an understanding of nursing practice and behaviors regarding PFCR. The second tool is the format for a workshop for nurses that aims to promote discussion about and interest in PFCR, as well as to empower nurses to be successful participants on PFCR. Additionally, we demonstrate how, by using information from the nursing survey, we were able to identify and address the largest barrier to nursing attendance on PFCR. Lastly, we provide a clinical practice guideline on PFCR, which gives information on best practices relating to rounds and a flow diagram of our approach to PFCR. This clinical practice guideline includes information about the coordination of this nursing initiative with other training that has been undertaken at our institution regarding PFCR. Nurses are an important part of patient care, and their presence on rounds is essential. Our quality-improvement project successfully improved the nursing attendance on PFCR from a baseline of 47% to 80%. The workshop for nurses was very well received by the nurses, with strong ratings and positive comments.